2008
DOI: 10.1248/cpb.56.57
|View full text |Cite
|
Sign up to set email alerts
|

N-Heterocyclic Carbene Ligands in Copper-Catalyzed Addition of Diethylzinc to N-Sulfonylimines

Abstract: N-Heterocyclic carbenes (NHCs) are strong s-donating species, showing coordination properties similar to those of phosphines.1,2) Initially, the widespread use of catalysts containing carbene ligands was limited due to their relatively difficult preparation. Since the discovery of stable carbenes by Arduengo 3) in 1991, interest in the use of N-heterocyclic carbene-metal complexes have increased, and it has been demonstrated that they are efficient catalysts in important chemical transformations such as Pd-cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…6 Since then different groups have studied this reaction with different chiral catalysts; for example, Gong et al used copper-bidentate and tridentate bisoxazolines, 7 Wang et al used copper-chiral ferrocenyl amidophosphines, 8 Shi et al used copper-chiral binaphthylthiophosphoramides, 9 and Suziki et al used copper-N -heterocyclic carbenes. 10 As examples of diethylzinc addition to N-diphenylphosphinoyl arylaldimine, Charatte et al used copper-chiral phosphine ligands, 11 Ha et al used copper-diphosphine and thiophosphoramide ligands, 12 Wang et al used copperferrocenyl amino ketones, 13 Liao et al used copper-chiral tert-butanesulfinylphosphines, 14 and Yus et al used polymer-supported L-prolinol catalyst. 15 Besides N -sulfonyl and N -phosphinoyl imines, this reaction was also studied with BOC and formyl protected imines by Aleksakis et al 16 and Feringa et al 17 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…6 Since then different groups have studied this reaction with different chiral catalysts; for example, Gong et al used copper-bidentate and tridentate bisoxazolines, 7 Wang et al used copper-chiral ferrocenyl amidophosphines, 8 Shi et al used copper-chiral binaphthylthiophosphoramides, 9 and Suziki et al used copper-N -heterocyclic carbenes. 10 As examples of diethylzinc addition to N-diphenylphosphinoyl arylaldimine, Charatte et al used copper-chiral phosphine ligands, 11 Ha et al used copper-diphosphine and thiophosphoramide ligands, 12 Wang et al used copperferrocenyl amino ketones, 13 Liao et al used copper-chiral tert-butanesulfinylphosphines, 14 and Yus et al used polymer-supported L-prolinol catalyst. 15 Besides N -sulfonyl and N -phosphinoyl imines, this reaction was also studied with BOC and formyl protected imines by Aleksakis et al 16 and Feringa et al 17 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Moreover, NHCs have attracted considerable attention as organocatalysts in several reactions such as benzoin condensation, [15][16][17][18][19][20] Stetter reaction, [21][22][23] transesterification/acylation reactions, 24,25) and nucleophilic substitution reactions. [26][27][28] In our study on the use of NHCs as ligands in organic transformations, we have recently reported the addition of diethylzinc to N-sulfonylarylimines catalyzed by Cu-NHC complexes, 29) where NHCs exhibit a strong ligand acceleration effect (LAE). This finding has prompted us to investigate the applicability of a similar methodology to the Rh-NHC complex-catalyzed addition of phenylboronic acid to imines.…”
mentioning
confidence: 99%